Sustainable synthesis routes towards urazole compounds. Issue 23 (8th November 2017) - Vlaminck, Laetitia; Van de Voorde, Babs; Du Prez, Filip E.
Abstract : The synthesis of urazoles in a one-pot, fast and high-yielding fashion without the use of isocyanates or chloroformates is described. Abstract : Sustainable synthesis routes towards urazoles, the precursor molecules for triazolinediones, are reported. Not only is the use of isocyanates avoided, but the applied synthetic procedures are also mostly solvent-free, high yielding and performed in an equimolar manner. Two complementary synthesis routes have been developed starting from a wide range of amines, both based on the use of diphenyl carbonate. The first method, which is particularly suitable for the synthesis of bulk urazoles, such as butyl, cyclohexyl or benzyl urazole, is performed in bulk in a one-pot fashion and generally results in yields between 87% and 96%. The second synthesis route, with yields up to 95%, focusses on the implementation of functionalities in the urazole structure and offers the possibility to generate bifunctional urazole compounds.